FEATURES OF SCIENTIFIC COMMUNICATION IN THE ERA OF INFORMATION TECHNOLOGY - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article investigates the features of the most recent systems of scientific communication in the era of information technology.